KAJIAN MINA WISATA SEBAGAI ALTERNATIF WISATA BAHARI DI KAWASAN PULAU SEMBILAN KABUPATEN SINJAI - Beddu Tang; Asmidar Asmidar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2019)
Sinjai Regency has a coastline of ± 41.06 km consisting of ± 23.7 km of land area and ± 17.36 km of archipelago. The population of the coast is 85,167 people (BPS, Sinjai District 2016). This condition certainly provides opportunities for a variety of utilization businesses including the development and improvement of the tourism sector.The purpose of this study are: 1) To examine the potential of the nine island fisheries natural resources in supporting marine tourism activities. 2) To determine the level of land suitability in an effort to ensure the sustainability of fisheries natural resources on Pulau Sembilan. While the benefits of this research are expected as follows: 1) Can be a guideline in the development and management of tourism mina on Pulau Sembilan. 2). It is expected to be a source of information for tourism management and reference for further research.This research was conducted in the Sembilan Island area, Sinjai Regency, South Sulawesi Province. The study was conducted for 2 (two) months, from October to November 2018. The data used in this study were primary data and secondary data.The results of this study indicate that the Sembilan Island fisheries sector has great potential to be developed in the future as a marine tourism object. Seaweed cultivation and floating net cages are fisheries commodities in this region. Pulau Sembilan has an area that is very supportive for the development of seaweed cultivation and floating net cages with an area of coastal waters ± 3,831.72 Km².